Focused ultrasound ablation of a large canine oral tumor achieves efficient tumor remission: a case report. (1st January 2021) - Ranjan, Ashish; Kishore, Deepan; Ashar, Harshini; Neel, Tina; Singh, Akansha; More, Sunil
Abstract: Purpose: Oral cancers are one of the commonly diagnosed tumors worldwide in human and veterinary patients. Most oral cancers are surgically resected; however, obtaining an adequate margin of safety in patients without compromising their quality of life is often challenging. Herein, we investigated the ability of non-invasive focused ultrasound (FUS) to thermally ablate a biopsy confirmed canine oral cancer. Materials and Methods: A male canine patient with a large neurilemmoma (schwannoma) mass on the left maxilla, with evidence of thinning and loss of alveolar bone and pressure necrosis, was treated with FUS ablation instead of the traditional maxillectomy procedure. FUS ablations were performed in three sessions over three weeks. Tumor remission was determined with computed tomography and histopathological examination of the treated site. Additionally, the anti-tumor immune effects of FUS were assessed by flow cytometry analysis of blood and tumor samples. Results: Complete tumor remission was noted at the treated site. Treatment related adverse events were primarily thermal burns of the buccal mucosa, which were managed with periodic hyperbaric oxygen therapy and surgical coverage of the underlying exposed bones with gingival flaps. Enhanced proliferation of adaptive immunity cells (e.g., T-cells) was observed in tumor and blood samples. Conclusion: Our limited investigation in a canine oral cancer patient suggests that FUS may avoid the need for large-scale resection of bony tissues, thus potentially improving quality of life.